2003
DOI: 10.1002/ardp.200390003
|View full text |Cite
|
Sign up to set email alerts
|

Brain Delivery of HIV Protease Inhibitors

Abstract: To overcome the problems of peptidomimetic drug delivery to the specific organs, the use of dihydropyridine <--> pyridinium chemical delivery systems to deliver peptides to the brain is considered in this work. An HIV protease inhibitor lead compound; KNI 279 was selected for the study. The N-alkylated dihydroisoquinoline derivatives of KNI-279 were synthesized and tested for their ability to be oxidized by brain homogenate and showed good results with reasonable half-life times specially for the N-alkoxycarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 8 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…The first reported substrate analogue design studies revealed that hepta peptide [41][42][43], reduced bond isosters L-Y-[CH 2 -NH]-L-P and L-F-[CH 2 -NH]-L-P inhibited HIV PR-catalysed hydrolysis of related all-L peptide (Ac-SQNYPVV-NH 2 ) with K i values 10 3 times lower than K m value for the substrate. Subsequent studies comparing various isosters with identical flanking peptide sequences indicated that the reduced amide isoster was the least effective of those tested.…”
Section: Pseudopeptides As Transition-state Analogues Structure-basedmentioning
confidence: 98%
See 1 more Smart Citation
“…The first reported substrate analogue design studies revealed that hepta peptide [41][42][43], reduced bond isosters L-Y-[CH 2 -NH]-L-P and L-F-[CH 2 -NH]-L-P inhibited HIV PR-catalysed hydrolysis of related all-L peptide (Ac-SQNYPVV-NH 2 ) with K i values 10 3 times lower than K m value for the substrate. Subsequent studies comparing various isosters with identical flanking peptide sequences indicated that the reduced amide isoster was the least effective of those tested.…”
Section: Pseudopeptides As Transition-state Analogues Structure-basedmentioning
confidence: 98%
“…Antibodies raised against the modified reduced amide epitope were specifically able to recognise those native antigen's structural features which could not be mimicked by the natural all-L amino acids peptide (MSP-1 [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] ). These findings have revealed that receptors on RBC for the MSP-1 42-61 epitope are fairly selective for L-natural conformations on amino acid ligands which (as shown) can be mimicked by specific -[CH 2 -NH] modifications; so, inducing modulated molecular [CH 2 -NH] surrogate antibodies can differentiate topochemistry but not chirality.…”
Section: L-amino Acid--[ch 2 -Nh]-l-amino Acid Malaria Pseudopeptidesmentioning
confidence: 99%
“…Isoquinoline skeletons are seen within a large number of naturally occurring, biologically active, synthetic heterocyclic compounds , including such drugs as papaverine . Moreover, 1,2‐dihydroisoquinoline derivatives act as delivery systems that transport drugs through the otherwise highly impermeable blood–brain barrier and exhibit sedative , antidepressant , antitumor, and antimicrobial activities .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most of the FDA-approved PIs are known substrates of the human multidrug-resistance gene (MDR1) transporter, P-glycoprotein (P-gp), which limits their transport across the BBB to the CNS [6]. Approaches such as developing potent PI derivatives [7], prodrugs (e.g., azidothymidine [8, 29] or using P-gp inhibitors [10] have been investigated to enhance the CNS bioavailability of anti-HIV drugs. However, developing new drugs or prodrugs could be an extensive undertaking with uncertain future.…”
Section: Introductionmentioning
confidence: 99%